The Influence of Leadership Style and Organizational Culture on Work Motivation and Its Impact on Employee Productivity at PT APL Commercialization Division - Agus Juanda; Vip Paramarta; Sobarna Kartamihardja (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
The pharmaceutical industry is experiencing significant changes due to rising demands for innovation, pricing pressures, and complex regulations. PT Anugerah Pharmindo Lestari (APL) faces similar challenges in Southeast Asia, including Indonesia. As a digitalization pioneer in pharmaceutical distribution, APL's Commercialisation Division experiences a paradox: sales continue to grow, yet employee productivity does not increase proportionally. This study investigates the impact of leadership style and organizational culture on employee productivity, with motivation as a mediating variable. Using a causal-descriptive method with a cross-sectional design, 85 out of 555 employees were selected through stratified random sampling based on the Slovin formula. Data were collected via Google Forms and analyzed using Path Analysis in SPSS 26 after passing validity, reliability, and classical assumption tests. Most respondents were male, aged 41–50, worked in sales, and had 5–10 years of tenure. Descriptive results show that leadership style, culture, and motivation fall into the excellent category (average 4.21–5.00), while productivity remains in the good category (3.41–4.20). Hypothesis testing reveals that organizational culture and motivation significantly affect productivity. Motivation mediates the effect of organizational culture but does not mediate leadership style. Leadership style also does not directly influence productivity.